Critical success factors for blockchain integration in the Malaysian construction industry - Tohfa, T. S.; Raihah, Mohamed Adzha; Lee, Yong Siang; Almutairi, Saud (IOP Publishing Ltd., 2025)
Blockchain introduces a decentralized and secure database structure, allowing multiple parties to access and verify information in real-time. Potentiality for enhance transparency and efficiency, blockchain’s integration in the Malaysian construction industry remains challenging due to the industry’s conservative nature and resistance to integrating new technologies. The study identifies the critical success factors of blockchain integration in the Malaysian construction industry, examine similarities and differences, and explore the interrelationships between these factors. A questionnaire survey targeting professionals engaged in various construction processes garnered 123 responses. These responses were analyzed using normalized mean, agreement, and overlap analyses. The study identifies 22 CSFs for blockchain integration in the Malaysian construction industry, emphasizing data security, cost efficiency, and data integrity. It highlights shared priorities and differences among stakeholders, strong correlations between CSFs, and consistent criticality of success factors across different organization types, offering key insights for blockchain integration. The results provide new evidence on the CSFs for successful blockchain integration, contributing to a framework that can help mitigate risks and overcome barriers associated with integrating blockchain in the Malaysian construction industry.